PSYCHOLOGICAL CHARACTERISTICS OF AGGRESSION IN CHILDREN OF YOUNGER SCHOOL AGE - Величко, Ольга (SWorldJournal, 2024)
The article reveals the psychological features of aggressiveness among children of primary school age. The essence of the concept of "aggression" is presented. It was established that children who witnessed their parents' aggression reproduce what they sa